Physical analysis of semiconductors materials and devices - Aung, Myo Sint (2012)
This project concerns the measurements and characterization of GaAs/Si direct wafer bonding and devices using optical and electrical methods. The limitations that lie within GaAs/Si direct wafer bonding will be identified and given improvised solutions. Dry plasma treatment is used before bonding of the two substrates. The effects of plasma parameters (i.e. RF power, chamber pressure, gas flow rate and type of gas used) on activated surface will be analyzed and modeled using theoretical methods and compared to the measurement data using analytical models. We will not only focus on the high bond energy (surface energy) but also the bonding density, the amount of available atomic sites to be bonded at the interface due to void occurrence. The best result comes so far from the experiments are the RF Power of 100 Watts, chamber pressure of 100 mtorr and plasma exposure of 5 seconds while using argon gas. From this research, it could have impact on current semiconductor technology’s bonding process and overall integration process.